Beyond Terrorism: An Interdisciplinary Legal Study of The Motivation, Impact, and Solidarity of Lone Wolf Terrorism: Melampaui Terorisme: Studi Hukum Interdisipliner tentang Motif, Dampak, dan Solidaritas Terorisme Lone Wolf - Samsul Arifin; Achmad Hariri; L.ya Esty Pratiwi; Agus Supriyo (Universitas Negeri Semarang, 2025)
Lone wolf terrorism is terrorism committed by individuals without direct affiliation with large terrorist organizations. This phenomenon is increasingly worrying in various countries, including Indonesia. Attacks by self-radicalized individuals have a different pattern from conventional terrorism, as the perpetrators act alone and are difficult to detect by security forces. In Indonesia, the increase in Lone Wolf terrorism cases in recent years is due to the easy access to the internet and social media that spread radicalism. The city of Surabaya came under scrutiny after the terrorist attacks in May 2018, where several acts were linked to large networks such as Jamaah Ansharut Daulah (JAD). The government and local communities, such as the Community of Peace Fighters, have tried to prevent radicalization through deradicalization programs and monitoring of vulnerable individuals. However, the individualistic and disorganized nature of lone wolf terrorism makes it difficult to anticipate. This research aims to identify patterns of radicalization that can give rise to lone terrorists, who are not directly affiliated with terrorist groups. The method used is interdisciplinary legal research with a qualitative approach, which was carried out at the Surabaya Peace Fighters Community, which is under the guidance of the Special Da'wah Institute (LDK) of the Muhammadiyah Regional Leadership (PWM) of East Java. The results of this study show that there are so many external factors that make a person radicalized. One of them is ideological factors, social conditions, structural injustices that encourage them to rebel, and the most powerful is the understanding that radical actions are justified by religious teachings (Islam).